2010
DOI: 10.4103/1319-1683.74332
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effect of health education on mothers in Al Maki area, Gezira state, to improve homecare for children under five with diarrhea

Abstract: Introduction:Home care of under-five children is one of the most important interventions in the control of diarrheal diseases. It has a significant impact in reducing childhood mortality and morbidity.Objective:This study was conducted to evaluate the effect of health education on home care of under- five children with diarrheal disease.Materials and Methods:This is a quasi- experimental study, held in Al Maki neighborhood, which is located in Greater Wad Medani locality, Gezira State, Central Sudan. The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 3 publications
(2 reference statements)
2
10
0
Order By: Relevance
“…In this study the respondents were mothers having children under-five years old. Significant improvement in mothers’ knowledge after the intervention as regards diarrhea and its management was consistent with the findings of other studies ( Haroun, Mahfouz, Mukhtar, & Salah, 2010 ; Karamagi, Lubanga, Kiguli, Ekwaru, & Heggenhougen, 2004 ), proving that health education using CHWs is an effective means of improving mothers’ competence in caring for their children at home during episodes of diarrhea.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In this study the respondents were mothers having children under-five years old. Significant improvement in mothers’ knowledge after the intervention as regards diarrhea and its management was consistent with the findings of other studies ( Haroun, Mahfouz, Mukhtar, & Salah, 2010 ; Karamagi, Lubanga, Kiguli, Ekwaru, & Heggenhougen, 2004 ), proving that health education using CHWs is an effective means of improving mothers’ competence in caring for their children at home during episodes of diarrhea.…”
Section: Discussionsupporting
confidence: 88%
“…In the current study, the mean total knowledge score of mothers was 13.8 ± 3.9 SD, which increased in the post- test to 19.1 ± 0.9 SD. The above findings were supported by a similar study conducted in Al Maki area, Gezira state, which revealed that health education caused a significant improvement in mothers’ knowledge and practice with respect to homecare of under-five children with diarrhea ( Haroun et al, 2010) .…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In order to mitigate diarrheal disease, health and food safety education plays an important role as well as the factors (Sheth and Obrah, 2004;Haroun et al, 2010;Mashoto et al, 2014;Abdel-Aziz et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Diarrhea is defined as the passage of three or more loose or watery stools in 24-hour duration. 1 According to 2011 NDHS, 14 percent of all children under five had diarrhea with 2 percent having diarrhea with blood. Young age, poor nutritional status, dehydration, and lack of breastfeeding are the major risk factors for death from diarrhea.…”
Section: Introductionmentioning
confidence: 99%